Dormansi Benih Melon (Cucumis melo L.): Penyebab, Tipe, dan Efektivitas Perlakuan Plasma untuk Pematahan Dormansi: Seed Dormancy of melon seed and it’s breaking - Setyowati, Nur Farida; Suhartanto, M. Rahmad; Purwanto, Y. Aris (Jurnal Hortikultura Indonesia, 2025)
Freshly harvested melon seeds exhibit dormancy, resulting in a germination rate of less than 45%. Plasma, an ionized gas, produces reactive oxygen species (ROS) and reactive nitrogen species (RNS) that enhance seed imbibition. This study aimed to identify the type of dormancy in melon seeds and evaluate the effects of plasma treatment through two experiments. The first experiment assessed the physiological quality of seeds over 10 weeks and measured hormone concentrations in seeds stored for 0 to 5 weeks. For seeds stored for 7 weeks, we peeled the testa and tegmen. The second experiment tested plasma effects on freshly harvested seeds by applying it at voltages of 100, 150, and 225 volts for 120 seconds, both on dry seeds and those moistened for 1 hour. We also optimized soaking times (2, 4, or 6 hours) for seeds with a 4-week shelf life at 225 volts. Results showed fluctuating levels of gibberellin (GA) and abscisic acid (ABA) hormones, with peeling increasing the germination rate to 89%. Seeds treated with plasma exhibited higher GA concentrations than the control, and a 2-hour soaking before 225-volt plasma application increased the germination rate to 83.5%. In conclusion, melon seeds demonstrate both physical dormancy (due to a non-permeable seed coat) and physiological dormancy (linked to hormonal balance). Keywords: ABA, GA, germination, RNS, ROS